HOW TO ENHANCE ORAL PROFICIENCY IN OUR LEARNERS - DERRADJI, Saleh (Journal of Human Sciences, 2008)
The aim of this paper is to examine some adequate oral techniques in English for Specific Purposes situation (ESP) which will develop genuine oral communication in the students of commerce (National institute of commerce,Algiers) .We believe that this article will be beneficial to teachers of English in that it will provide them with the and appropriate techniques to help the students to develop their speaking skill, as we believe that our learners must be given true opportunities throughout their years of study to enhance the skill of encoding their thoughts in the foreign language.The investigation was led through two questionnaires (one for the students another for the teachers) in order to build up an expression of the learners needs and specify the objectives of the techniques to be proposed for this population of learners.The results revealed that the students of commerce are aware of learning English in general, as they have shown that their primary preference / concern is to enhance their ability to communicate orally in English. Consequently, some oral techniques are proposed by the writer to develop the student’s ability to communicate in the target language.